The effects of Emotional Intelligence on the Organizational Climate (JÓVENES EN LA CIENCIA, 2023)
This article presents the results obtained from a theoretical review on the concepts of Emotional Intelligence, Organizational Climate and the relationship between them. Based on exhaustive research, Emotional Intelligence is defined as a psychological construct that includes various personality traits that allow for the recognition of our own emotional and affective reactions and states, self-motivation, emotional regulation, empathy, and social skills to establish bonds with others. For instance, the Organizational Climate is defined as the psychological and cognitive perception that employees have of their work environment, as well as its evaluation. Several investigations indicate that there is a significant relationship between both concepts, being that Emotional Intelligence promotes a positive Organizational Climate and stimulates productivity and the achievement of the objectives established by the organization, although there are other research papers whose results highlight the null link between both variables or the existence of an inverse relationship.